Two ectomycorrhizal truffles, Tuber melanosporum and T. aestivum, endophytically colonise roots of non‐ectomycorrhizal plants in natural environments. Issue 6 (16th December 2019) - Schneider‐Maunoury, Laure; Deveau, Aurélie; Moreno, Myriam; Todesco, Flora; Belmondo, Simone; Murat, Claude; Courty, Pierre‐Emmanuel; Jąkalski, Marcin; Selosse, Marc‐André
Summary: Serendipitous findings and studies on Tuber species suggest that some ectomycorrhizal fungi, beyond their complex interaction with ectomycorrhizal hosts, also colonise roots of nonectomycorrhizal plants in a loose way called endophytism. Here, we investigate endophytism of T. melanosporum and T. aestivum . We visualised endophytic T. melanosporum hyphae by fluorescent in situ hybridisation on nonectomycorrhizal plants. For the two Tuber species, microsatellite genotyping investigated the endophytic presence of the individuals whose mating produced nearby ascocarps. We quantified the expression of four T. aestivum genes in roots of endophyted, non‐ectomycorrhizal plants. Tuber melanosporum hyphae colonised the apoplast of healthy roots, confirming endophytism. Endophytic Tuber melanosporum and T. aestivum contributed to nearby ascocarps, but only as maternal parents (forming the flesh). Paternal individuals (giving only genes found in meiotic spores of ascocarps) were not detected. Gene expression of T. aestivum in non‐ectomycorrhizal plants confirmed a living status. Tuber species, and likely other ectomycorrhizal fungi found in nonectomycorrhizal plant roots in this study, can be root endophytes. This is relevant for the ecology (brûlé formation) and commercial production of truffles. Evolutionarily speaking, endophytism may be an ancestral trait in some ectomycorrhizal fungi that evolved from root endophytes.